Case Report: Malignant Primary Sellar Paraganglioma With Unusual Genetic and Imaging Features - Stojanoski, Stefan; Boldt, Henning Bünsow; Kozic, Dusko; Patócs, Attila; Korbonits, Márta; Medic-Stojanoska, Milica; Casar-Borota, Olivera (Frontiers in Oncology, 2021)
Background: Paraganglioma occurs rarely in sellar/parasellar region. Here we report a patient with malignant paraganglioma with primary sellar location with unusual genetic and imaging features. Case presentation: A 31-year-old male presented with mild hypertension, headache, nausea and vomiting. A sellar/parasellar tumour mass was revealed by magnetic resonance imaging (MRI), while an endocrine work-up found partial hypopituitarism suggesting that it was a non-functioning pituitary tumour. Antihypertensive therapy and hormone replacement was initiated. Tumour reduction was achieved with transsphenoidal neurosurgery. However, histological diagnosis was not possible due to extensive tissue necrosis. After four years of stable disease, the residual tumour showed re-growth requiring gamma knife radiosurgery. Four years after the radiosurgery, MRI showed a significant tumour progression leading to second neurosurgery. This time, pathological and immunohistochemical findings revealed paraganglioma. Plasma levels of metanephrine and normetanephrine were normal. A gene sequencing panel performed on DNA extracted from blood excluded germline mutations in 17 susceptibility genes. The patient developed new tumour masses in the neck, the third surgery was performed. Immunohistochemistry demonstrated a lack of ATRX (alpha thalassemia/mental retardation syndrome X-linked) protein in tumour cells indicating an ATRX gene mutation. Molecular genetic analysis performed on tumour DNA revealed a combination of ATRX and TP53 gene abnormalities, this was not previously reported in paraganglioma. MRI and 68Ga-DOTANOC PET/CT revealed the full extent of the disease. Therapy with somatostatin LAR and 177Lu- DOTATATE Peptide Receptor Radionuclide Therapy (PRRT) was initiated. Conclusion: Although rare, paraganglioma should be considered in the differential diagnosis of sellar/parasellar tumour lesions, even in the absence of typical imaging features. ATRX gene mutation in paraganglioma is an early predictor of malignant behaviour and a potential novel therapeutic marker when pharmacological therapy targeting mutated ATRX becomes available.